THE EFFECTIVENESS OF E-LEARNING LEARNING IN THE PANDEMIC TIME IN AUTOMOTIVE ENGINEERING BASIC WORKS CLASS X SMKN 1 KUALA DURING THE ACADEMIC YEAR 2021/2022 - Abdul Rosid Rosid; Revianti Coenraad (Jurusan Pendidikan Teknologi Dan Kejuruan, 2022)
This study aims to find out how much the Effectiveness of E-Learning in the Pandemic Period in the Automotive Engineering Basic Work Subject. This study uses the research method used in this study is a qualitative descriptive research method. The subject of this study is the effectiveness of e-learning in the Automotive Engineering Basic Work subject using the online media Zoom Meeting during the Covid-19 pandemic by class X students. Automotive in the odd semester of the 2021/2022 school year. The object of research in this study were Deputy Head As if, Supporting Teachers for Basic Automotive Engineering subjects and Shiva class X. Data collection used Interview and Documentation methods. The collected data is then analyzed as a result of the research. The results of the study show that e-learning uses online media during the Covid-19 pandemic in the field of basic automotive engineering, class X students of SMKN 1 Kuala Kurun in the 2021/2022 academic year online during the Covid-19 pandemic using zoom meeting media is quite effective, but still not optimal and less efficient. This is caused by repeated boredom so that it reaches a saturation point. In addition, the material that students are able to absorb is less than half, coupled with the ability of teachers and students to use the internet which is still low. Thus online learning is felt to be quite effective when it is only done intermittently, not continuously for 1 semester.